The Application of PAI Teachers in Developing Islamic Awareness to Students and The People of Papua Through Broadcast (Approach) - Hilmatul Asfiyah (Yayasan Literasi Altruis Khatulistiwa, 2025)
Papua is known for its non-Muslim population, but the opposite fact shows that the Islamic community has been established since 1512. Therefore, it is relevant to explore the existence of Muslims in West Papua Province with current conditions. This research uses a qualitative approach with the type of grounded theory. In collecting data, observation and in-depth interviews are used. The main instrument is the researcher himself, then accompanied by observation guidelines and interview guides. This research shows that there are three findings, namely leadership and customs, religiosity and diversity, and the spirit of learning. The main findings show that Muslims in the region, especially in West Papua itself, not only try to maintain their traditions but also always maintain religious harmony with other people. This attitude does not arise spontaneously, there is a very long historical journey so that they can coexist with others as a family. However, not all of them can accept it because some of these people still want to separate themselves from Indonesia because for them Papua has its own independence.